The Influence of Altman Z-Score Bankruptcy Prediction Model on Stock Prices in the Textile and Garment Sub-Sector Companies - Muhazir, M. Rony; Alwi, Alwi; Herman, Herman (Journal of Economics, Management and Accounting (JEMA), 2024)
This research aims to help investors evaluate the financial health of companies listed on the IDX. The Altman Z-Score model, given by Z = 1.2 X1 + 1.4 X2 + 3.3 X3 + 0.6 X4 +1,0 X5 This study also examines the impact of the Z-Score on stock prices, which is recorded after a company releases its financial reports. A total of 3 manufacturing companies were selected for research using purposive sampling. The results of the Z-Score calculation show that there are no companies that are potentially on the verge of bankruptcy, all three companies are in the safe zone, and this shows that they are financially healthy. Simple regression analysis shows that the Z-Score value has a direct effect on stock prices. Likewise, the value of the T Test results has a significant influence on stock prices. The objective of this study is to ascertain if there is a significant correlation between the Altman Z-Score and the volatility in a company's stock price. The results of this investigation could offer valuable insights for investors, financial analysts, and stakeholders in making informed decisions and risk evaluations.